Diseño, construcción, montaje y puesta en marcha de un sistema de reacción con lecho fijo catalítico (PBR) para obtención de cinéticas de reacción (2005)
The design of the plug bed reactor (PBR) can be used as a differential or integral reactor. For the porpuse of this research, the reactor is used as a differential allowing the achievement of reactions kinetics, in this case the DBT (dibenzothiophene) Hydrodesulphurization reaction. The reactor is 61 cm height, 1.587 cm. Of outlet diameter, and 1.320 cm of inlet diameter. It permits the handling of a liquid flowrate between 0,01 and 10 ml./min, a two inlet gas flowrate varying from 0,0081 ml./min. To 30 ml./min and an operative pressure between 3 and 60 atm. It also includes a heating zone by a spit tubular furnace which handles temperaturas from 30 to 550° C. The above configuration characteristics results in a wide versatility in the reactor operational conditions and allows the analysis of gas and liquid-gas reactions. Fort he Hydrodesulphurization reaction the conditions are: 40 atm. of presure, 400 Hydrogen/DBT...